The validation of an educational database for children with profound intellectual disabilities - Karlien Spangenberg (African Journal of Disability, 2016)
Background: The Western Cape Forum for Intellectual Disability took the South African Government to court in 2010 on its failure to implement the right to education for Children with Severe and Profound Intellectual Disability. Subsequently, multidisciplinary teams were appointed by the Western Cape Education Department to deliver services to the Special Care Centres (SCCs). Initially, minimal information was available on this population. Objectives: The purpose is to document the process of developing and validating a database for the collection of routine data. Method: A descriptive analytical study design was used. A sample of convenience was drawn from individuals under the age of 18 years, enrolled in SCCs in the Western Cape. The team who entered and analysed the data reached consensus regarding the utility and feasibility of each item. Results: Data were collected on 134 children. The omission of certain items from the database was identified. Some information was not reliable or readily available. Of the instruments identified to assess function, the classification systems were found to be reliable and useful, as were the performance scales. The WeeFIM, on the other hand, was lengthy and expensive, and was therefore discarded. Discussion and conclusions: A list of items to be included was identified. Apart from an individual profile, it can be useful for service planning and monitoring, if incorporated into the central information system used to monitor the performance of all children. Without such inclusion, this most vulnerable population, despite court ruling, will not have their right to education adequately addressed.